Peran Sistem Informasi Berbasis Fintech dalam Meningkatkan Literasi Investasi Saham di Indonesia - Angga Saputra; Ardo Febio Josultan; Konny Setiawan; Sigit Reinaldi (CV. ITTC INDONESIA, 2025)
This study aims to explore in depth how information systems integrated with financial technology (fintech) play a crucial role in improving stock investment literacy in Indonesia. The rapid development of digital technology, particularly in the financial sector, has led to the emergence of various virtual platforms that provide easier access to investment services. This convenience has directly influenced shifts in financial behavior, especially among the younger generation who tend to be more adaptive to technology. Using a literature review approach, this study examines a range of scholarly articles, industry reports, and previous research to identify the concrete contributions of digital investment applications and educational fintech-based software in expanding public knowledge about the capital market. The study also highlights how information systems designed to be interactive and user-friendly can enhance understanding of fundamental investment concepts, risk awareness, and sound financial strategies. Findings from this review reveal that the synergy between fintech innovation and financial literacy programs plays a highly significant role in encouraging public participation in stock investment activities. Furthermore, the presence of integrated information systems also contributes to narrowing financial knowledge gaps across different age groups and education levels. Thus, the use of information technology in the fintech sector functions not only as a transactional tool but also as an effective learning instrument to improve financial inclusion and competence across Indonesian society.